Electronic charge transfer in cobalt doped fullerene thin films and effect of energetic ion impacts by x-ray absorption spectroscopy - Thakur, P.; Kumar, Amit; Gautam, S.; Chae, K. H. (ELSEVIER SCIENCE SA, 2011)
We report on the electronic charge transfer in cobalt doped fullerene thin films by means of near-edge x-ray-absorption fine structure (NEXAFS) spectroscopy measurement. Co-doped fullerene films were prepared by co-deposition technique and subjected to energetic ion irradiation (120 MeV Au) for possibly alignment or interconnect of randomly distributed metal particles. Polarization dependent NEXAFS spectra revealed the alignment of Co and C atoms along the irradiated ionic path. The structural changes in Co-doped as-deposited and ion irradiated fullerene films were investigated by means of Raman spectroscopy measurements. Downshift of pentagonal pinch mode A(g)(2) in Raman spectroscopy indicated the electronic charge transfer from Co atom to fullerene molecules, which is further confirmed by NEXAFS at C K-edge for Co-doped fullerene films. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TRANSITION-METAL OXIDES; FINE-STRUCTURE; CARBON NANOTUBES; C-60; NANOPARTICLES; PHOTOEMISSION; ADSORPTION; GRAPHITE; CLUSTERS; SPECTRA